Peningkatan nilai produk olahan hasil laut dan gerakan gemar makan ikan bagi kelompok istri dan anak nelayan guna mencegah stunting [Increasing the value of processed sea products and the fish-eating movement for groups of fisherman wives and children to prevent stunting] - Rachmawati, Kadek; Mulyati, Sri; Utama, Suzanita; Wurlina, W; Santoso, Kuncoro P.; Suwasanti, Ni Luh (Universitas Syiah Kuala, 2024)
This Community Service Activity is carried out to educate fishermen's wives on how to process marine products such as fish into processed foods that children like so that children will be more fond of eating fish, processed innovations using raw materials from marine products into dry products and wet products with high-quality nutritional value with high selling value, and increasing the love of eating fish among fishing families to increase intelligence and prevent stunting. The methods used are education, training, and mentoring for innovations in processed seafood which are popular with children and have high selling value, apart from that, education is also carried out about stunting and how to prevent stunting. The result of this PKM activity is that fishermen's wives can make various foods and snacks made from marine products that are popular with children and have value for sale so that they can provide income for fishermen's wives, as well as increase the understanding of fishermen's wives about stunting to prevent the incidence of stunting in fishermen's children and increase the movement for eating fish among fishermen's families.